Stabilized Long-Distance Superluminal Propagation Based on Polarization-Matched Low-Noise Brillouin Lasing Resonance - Liang Zhang (IEEE, 2022)
This paper comprehensively investigated noise characteristics of superluminal propagation based on low-noise single-frequency Brillouin lasing oscillation with the aid of a population inversion dynamic grating. Thanks to high-degree polarization alignment between the Brillouin pump and the lased Stokes lightwaves in polarization maintaining fibers, efficient Brillouin lasing resonance with over 10-dB relative intensity noise suppression has been demonstrated to activate Brillouin loss-induced anomalous dispersion in the vicinity of pump signals, benefiting a noise-insensitive superluminal propagation along kilometer-long optical fibers with robust resistance to ambient disturbance. Consequently, sinusoidally modulated pump signals experienced the time advancement of 4634.0 ns at the group velocity of 10.63c. Results show that the variance of the fractional advancement with polarization maintaining fibers is 2.54 × 10−4 which is two orders of magnitude lower than that of conventional single mode fibers. Furthermore, the dependence of the group velocity on the modulation frequency was experimentally investigated, showing good agreement with the theoretical analysis.